Responsive evaluation: an innovative evaluation methodology for workplace health promotion interventions - Tineke Abma; Cécile RL Boot; Hanneke van Heijster; Jantien van Berkel; Emely de Vet (BMJ Open)
Background: Workplace health promotion (WHP) interventions have limited effects on the health of employees with low socioeconomic position (SEP). This paper argues that this limited effectiveness can be partly explained by the methodology applied to evaluate the intervention, often a randomised controlled trial (RCT). Frequently, the desired outcomes of traditional evaluations may not match employees’—and in particular employees with low SEP—needs and lifeworld. Furthermore, traditional evaluation methodologies do not function well in work settings characterised by change resulting from internal and external developments. Objective: In this communication, responsive evaluation is proposed as an alternative approach to evaluating WHP interventions. Responsive evaluation’s potential added value for WHP interventions for employees with low SEP in particular is described, as well as how the methodology differs from RCTs. The paper also elaborates on the different scientific philosophies underpinning the two methodologies as this allows researchers to judge the suitability and quality of responsive evaluation in light of the corresponding criteria for good science.